A single strain of Mycobacterium bovis bacillus Calmette-Guérin (BCG) grown in two different media evokes distinct humoral immune responses in mice - Petricevich,V.L. (2001)
Two attenuated bacillus Calmette-Guérin (BCG) preparations derived from the same Moreau strain, Copenhagen but grown in Sauton medium containing starch and bacto-peptone (onco BCG, O-BCG), or asparagine (intradermal BCG, ID-BCG), exhibited indistinguishable DNA sequences and bacterial morphology. The number of viable bacilli recovered from spleen, liver and lungs was approximately the same in mice inoculated with the vaccines and was similarly reduced (over 90%) in mice previously immunized with either BCG vaccine. The humoral immune response evoked by the vaccines was, however, distinct. Spleen cell proliferation accompanying the growth of bacilli in tissue was significantly higher in mice inoculated with O-BCG. These cells proliferated in vitro upon challenge with the corresponding BCG extract. Previous cell treatment with mAb anti-CD4 T cells abolished this effect. Anti-BCG antibodies, as assayed either in serum by ELISA or by determining the number of antibody-producing spleen cells by the spot-ELISA method, were significantly higher in mice inoculated with ID-BCG. Anti-BCG antibodies were detected in all immunoglobulin classes, but they were more prevalent in IgG with the following distribution among its isotypes: IgG1>(IgG2a = IgG2b)>IgG3. When some well-characterized Mycobacterium tuberculosis antigens were used as substitutes for BCG extracts in ELISA, although antibodies against the 65-kDa and 96-kDa proteins were detected significantly, antibodies against the 71-kDa, 38-kDa proteins and lipoarabinomannan were only barely detected or even absent. These results indicate that BCG bacilli cultured in Sauton-asparagine medium permitted the multiplication of bacilli, tending to induce a stronger humoral immune response as compared with bacilli grown in Sauton-starch/bacto-peptone-enriched medium.